CULTURAL FACTORS AND THEIR IMPACT ON PROBLEM-SOLVING APPROACHES AMONG HIGHER EDUCATION STUDENTS IN WEST BENGAL (International Journal of Food and Nutritional Sciences, 2025)
This study explored the cultural factors that influenced problem-solving approaches among higher education students in West Bengal. The region's collectivist values, strong family expectations, traditional educational norms, and linguistic diversity significantly shaped students' engagement with academic challenges. The research highlighted how collectivism fostered group-based problem-solving strategies, while family pressures often led to structured, rote learning. Traditional educational practices that emphasized memorization limited creative thinking and independent problem-solving. However, with the shift towards interactive and problem-based learning, there was potential to encourage innovative problem-solving skills. The study emphasized the importance of balancing traditional methods with critical thinking and independent learning, while also acknowledging cultural contexts. By fostering an inclusive and culturally sensitive learning environment, the research aimed to enhance students' problem-solving abilities and prepare them for the complexities of the modern world. The findings suggested that understanding the interplay between culture and cognitive processes was essential for improving educational outcomes in West Bengal’s higher education system.